2021
DOI: 10.1111/jmcb.12880
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy, Inflation, and Rational Asset Price Bubbles

Abstract: Inflation has tended to be moderate during stock market booms in many countries. To explain the pattern and study optimal monetary policy in such a situation, this paper develops a dynamic model with rational bubbles and nominal rigidities. The model features a financial cost channel through which the shadow cost of borrowing affects marginal costs. A bubble‐led boom mitigates firms' borrowing constraints and keeps inflation from rising by decreasing the shadow cost. In this situation, Ramsey‐optimal monetary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The negative impact of inflation in Africa is reflected in the high cost of borrowing (Agoba et al, 2020b;Ikeda, 2021), high cost of living (Breinlich et al, 2017), and high levels of poverty (Meo et al, 2018). Many scholars have found that high inflation negatively affects poverty.…”
Section: Original Articlementioning
confidence: 99%
“…The negative impact of inflation in Africa is reflected in the high cost of borrowing (Agoba et al, 2020b;Ikeda, 2021), high cost of living (Breinlich et al, 2017), and high levels of poverty (Meo et al, 2018). Many scholars have found that high inflation negatively affects poverty.…”
Section: Original Articlementioning
confidence: 99%